2019
DOI: 10.1016/j.matpur.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Sharp estimates of the spherical heat kernel

Abstract: We prove sharp two-sided global estimates for the heat kernel associated with a Euclidean sphere of arbitrary dimension.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…We nevertheless prefer to keep using the terminology of S 2 , for the sake of simplicity. We will make use of the following properties of the heat kernel p(t, x, y) = p(t, θ), for which we refer to [27,29].…”
Section: The Case Of the 2-dimensional Spherementioning
confidence: 99%
“…We nevertheless prefer to keep using the terminology of S 2 , for the sake of simplicity. We will make use of the following properties of the heat kernel p(t, x, y) = p(t, θ), for which we refer to [27,29].…”
Section: The Case Of the 2-dimensional Spherementioning
confidence: 99%
“…Above estimates have been complemented with asymptotics in [22], which revealed that the behaviour of p B (t, x, y) is in fact driven by the expression δ x+y 2 / √ t. A similar property will be observed in general lower bound (5). We refer the reader to [3,4,5,12,19,20,21] for some other recent articles focused on sharp estimates of heat kernels in other settings.…”
Section: Introductionmentioning
confidence: 61%
“…L in (20). Furthermore, adding also the condition W (τ 1 ) ∈ {0} × I 0 under the expectation we arrive at…”
Section: Lower Boundsmentioning
confidence: 92%
“…Consequently, the heat kernel is appropriate for constructing nonlinear support vector machines for shapes' classification [43] . It is worth noting that to better grasp the significance of the heat kernel closed-form approximation in (11) it should be reminded that the straightforward resolution of heat equations is only feasible for a restricted set of classical manifolds [24][25][26][27] ; other approaches provide merely bounds of the heat kernel [28][29][30][31][32][33][34][35][36][37][38] . Furthermore, number of closed-form expressions have been proposed in the litterature to calculate the heat kernel on hyperspheres like k m S .…”
Section: Discussionmentioning
confidence: 99%